Characteristics of malignant tumors of digestive system and autoimmune diseases - Yin, Hang; Li, Qun (Frontiers in Genetics, 2023)
With the development of preoperative examination technology, endoscopic ultrasonography-guided fine-needle aspiration biopsy (EUS-FNA) has been widely used in preoperative pathological diagnosis. However, challenges remain in obtaining appropriate tissue samples and obtaining accurate pathological results to predict disease risk. Therefore, this study aimed to analyze the characteristics of digestive system malignancies and their autoimmune diseases, and to analyze the clinicopathological features, preoperative CT imaging features and pathological grades of pNENs of different pathological degrees of pNENs on the prognosis of pNENs. Experimental results showed that non-functioning pancreatic neuroendocrine tumors showed prominent surrounding hypervascular lesions on multiphase CT examination. Among them, arterial phase and portal venous phase were most clearly imaged at the end, and the degree of local vascular invasion could be used as an index to evaluate its resectability. The sensitivity of CT examination was 63% to 82%, and the specificity was 83% to 100%, depending on the size.